Bladder Paraganglioma: Three Cases Report and Literature Review - Yuan Y (Dove Medical Press, 2021)
Yaoji Yuan,1,2,* Zhengming Su,1,2,* Rui Zhu,1,2 Xiezhao Li,1,2 Guibin Xu1,2 1Department of Urology, The Fifth Affiliated Hospital of Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China; 2Key Laboratory of Enhanced Recovery After Abdominal Surgery, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guibin XuDepartment of Urology, The Fifth Affiliated Hospital of Guangzhou Medical University, 621 Gangwan Road, Guangzhou, Guangdong, People’s Republic of ChinaEmail gyxgb@163.comBackground: Bladder paraganglioma (BPG) is one of the rare neuroendocrine neoplasms that develops from neural crest cells. It categorizes into functional and non-functional types based on the catecholamines secretion. Currently, functional BPG is predicted in advance based on signs and symptoms of catecholamine excess, such as hypertension and “micturition attacks”. However, it is often overlooked because of its rareness. Misdiagnosis of a functional tumor may increase the risk of surgical intervention.Case Presentation: We reported 3 cases of BPG that they were admitted to the hospital due to abdominal pain or gross hematuria. Computed tomography (CT) scans showed space-occupying lesions in the bladders with diameters less than 3cm. There were no typical catecholamine excess symptoms before surgical intervention. Postoperative pathology confirmed BPG after removal of the tumor. We also analyze 69 cases of BPG that has been reported and found that 78.0% cases were functional among the tumors larger than 3cm.Conclusion: Bladder tumors larger than 3cm in diameter can serve as an additional predictor of functional BPG. Patients who are suspected should undergo magnetic resonance imaging (MRI) scans, 123/131 metaiodobenzylguanidine (MIBG) scan, and have their catecholamine levels tested. Once the diagnosis is confirmed, patients should be started on fluid replacement therapy and adrenergic blockade to abate the disorders associated with catecholamine excess.Keywords: bladder paraganglioma, cases report